Studies of heat capacity of 1D chains of Xe, N2 and CH4 by using adiabatic calorimeter; International Conference on Thermal Analysis and Calorimetry in Russia (RTAC-2016); Vol. 2 - Barabashko M. S. Maksim Sergeevich; Bagatskii M. I. Michail Ivanovich; Sumarokov V. V. Vladimir Victorovich; Ponomarev A. N. Aleksandr Nikolaevich (Section 7: Young researchers conference-school "Modern trends in Thermal analysis and calorimetry", 2016)
The heat capacities of 1D chains of adsorbates of xenon, nitrogen and methane in the outer grooves of bundles of single - walled carbon nanotubes closed at their ends (SWNTs) have been studied using an adiabatic calorimeter in the temperature intervals 2 - 85 K, 2 - 40 K and 2 - 60 K, respectively. Experimental heat capacities of 1D chains of xenon and nitrogen adsorbates are in good agreement with the calculations of the phonon heat capacity below 9 K. The model of formation of thermal single vacancies have been proposed for describing the sharp increase of heat capacity of 1D xenon chains above 28 K. The entropy, enthalpy and temperature dependence of the concentration of thermal vacancies have been calculated. It was found that the contribution of the nitrogen librations to the heat capacity of 1D chains is essential above 15 K. Character of the temperature dependence of heat capacity of 1D chains of methane below 12 K indicates on the presence of Schottky anomaly caused by the tunneling between the lowest energy levels of rotational spectra of A, T, and E - nuclear spin modifications of the methane molecules.